2017
DOI: 10.1007/s10964-017-0720-6
|View full text |Cite
|
Sign up to set email alerts
|

Can Locus of Control Compensate for Socioeconomic Adversity in the Transition from School to Work?

Abstract: Internal locus of control is associated with academic success and indicators of wellbeing in youth. There is however less understanding regarding the role of locus of control in shaping the transition from school to work beyond the more widely studied predictors of socioeconomic background and academic attainment. Guided by a socio-ecological model of agency, the current study examines to which extent internal locus of control, understood as an indicator of individual agency, can compensate for a lack of socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 55 publications
4
29
1
5
Order By: Relevance
“…When considering the potential compensatory role of agency-related capacities with regard to the effects of social origin on ultimate social status attained in adulthood, previous social science research has identified three different processes involving independent, cumulative, and compensatory effects (Damian et al 2015;Ng-Knight and Schoon 2017;Shanahan et al 2014;Schoon and Lyons-Amos 2017). The evidence so far is focused on the role of broad personality indicators (not discussed here), with some evidence also being available regarding the role of intentions, expectations and values, which are summarized here.…”
Section: Can Individual Agency Overcome Social Constraints?mentioning
confidence: 99%
See 1 more Smart Citation
“…When considering the potential compensatory role of agency-related capacities with regard to the effects of social origin on ultimate social status attained in adulthood, previous social science research has identified three different processes involving independent, cumulative, and compensatory effects (Damian et al 2015;Ng-Knight and Schoon 2017;Shanahan et al 2014;Schoon and Lyons-Amos 2017). The evidence so far is focused on the role of broad personality indicators (not discussed here), with some evidence also being available regarding the role of intentions, expectations and values, which are summarized here.…”
Section: Can Individual Agency Overcome Social Constraints?mentioning
confidence: 99%
“…Fourth, access to socio-economic resources, which in turn is shaped by social background, determines the extent to which agency can be mobilized and realized. Agency is less effective in situations where the socio-economic risks are over-powering (Duckworth and Schoon 2012;Ng-Knight and Schoon 2017). Parents in higher social positions generally have more access to financial, cultural and social resources that enable them to support the aspirations of their offspring (Evans 2002;Shanahan 2000;Schoon 2010Schoon , 2012.…”
Section: To What Extent and Under Which Circumstances Can Agency Be Mmentioning
confidence: 99%
“…while individuals' locus of control may affect their educational attainment only indirectly, through study behavior, motivations, and aspirations. However, given the existing evidence that locus of control significantly affects individuals' labor market behavior and outcomes (see, e.g., Caliendo et al, 2015;Ng-Knight & Schoon, 2017;Osborne Groves, 2005), one may expect locus of control to play a more important role in mediating the parental class effect on individuals' labor market position. Conversely, the role of cognitive ability in mediating the parental class effect on individuals' social class position may be smaller than with respect to educational attainment, given that employers are likely to gauge applicants' cognitive ability mainly based on their level of education (Gottfredson, 1985).…”
Section: Me Thods and Re Sultsmentioning
confidence: 99%
“…The significant distribution in the effectiveness of the projects analyzed by Heckman, including negative values, points to the lack of readily available and tested solutions on the part of the education community for fostering noncognitive skills (especially among older children and teenagers). It is therefore easier to figure out how to stimulate self-sufficiency, grit, and other such traits in individuals than it is to adapt education systems towards developing personality traits [Ng-Knight, Schoon, 2017]. The leading research centers are working hard towards developing corresponding metrics but are still far from reaching this goal.…”
Section: New Findings In the Study Of Human Capital And Their Impact mentioning
confidence: 99%